Medicinal Orchids of Mexico: A Review - Luis J. Castillo-Pérez; Amauri Ponce-Hernández; Angel Josabad Alonso-Castro; Rodolfo Solano; Javier Fortanelli-Martínez; Luicita Lagunez-Rivera; Candy Carranza-Álvarez (MDPI AG, 2024)
Some species of the Orchidaceae family are used in Mexican traditional medicine. However, there are no current and critical compilations of the medicinal uses and pharmacological effects of the members of the Orchidaceae family. This review provides a current, critical, and comprehensive analysis of the traditional medicinal uses, pharmacological reports, and active compounds isolated from Mexican orchids. A total of 62 Mexican orchids with medicinal potential have been recorded, of which 14 have scientific evidence. The remaining 48 plant species have ethnomedicinal information but have not been validated with scientific studies. These orchids are distributed in 14 states of the Mexican Republic, mainly in the southern region of Mexico. The most common pharmacological activities reported are anti-inflammatory, vasorelaxant, antinociceptive, antioxidant, spasmolytic, antihypertensive, and hallucinogenic activities. It is necessary to increase the number of pharmacological, phytochemical, and toxicological studies with medicinal orchids from Mexico because there are scientific studies on only 22.5% of these species. In further studies, it will be possible to evaluate the pharmacological effects of Mexican orchids in clinical trials. In addition, the mechanisms of action by which plant extracts and their active compounds exert medicinal effects remain to be studied. Plant extracts from orchids and their active compounds show promising antinociceptive and spasmolytic effects, respectively.